Trajectories of health behaviors across early childhood cancer survivorship. Issue 1 (6th November 2018) - Fisher, Rachel S.; Rausch, Joseph R.; Ferrante, Amanda C.; Prussien, Kemar V.; Olshefski, Randal S.; Vannatta, Kathryn A.; Compas, Bruce E.; Gerhardt, Cynthia A.
Abstract: Objective: The majority of childhood cancer survivors develop at least one late effect subsequent to treatment (eg, cardiovascular disease and obesity). Consistent engagement in recommended health behaviors may mitigate some of these conditions. Researchers have identified early survivorship as a teachable moment, yet few studies have examined positive health behaviors during this period. Methods: Families of children with cancer (ages 5‐17) were initially recruited following a diagnosis or relapse of cancer. Three years post diagnosis, survivors (n = 82, Mage = 13.3, SD = 3.7) and their mothers (n = 103, Mage = 41.1, SD = 7.6) completed a questionnaire assessing exercise, dietary, and sleep patterns among survivors. A follow‐up assessment was conducted 2 years later. Mixed models tested change in health behavior over time. Results: At 3‐ and 5‐year post diagnosis, mother and self‐report indicated that few survivors engaged in appropriate levels of low‐intensity exercise, fruit/vegetable intake, and dairy consumption. However, most survivors engaged in recommended levels of high intensity exercise, fast food restriction, and sleep. Health behaviors remained stable over time, except for mother report of sleep duration, which decreased ( b = –0.6, P < 0.001). Brain tumor diagnosis predicted a larger decrease in self‐report of sleep duration compared with other diagnoses ( P = 0.04). Income predicted fast food intake such that higher income was associated with decreased intake over time, whereas lower income was associated with increased intake ( P = 0.04). Conclusions: During early survivorship, several health behaviors fell short of expectations for exercise and diet and did not improve upon reaching 5‐year post diagnosis. Providers should evaluate survivors' health behaviors, including sleep, early and often, intervening when necessary.